Bach Flower Remedies Healing According to Emotions (Homoeopathy for All, 2025)
Psychological imbalances if they  persist for a long time leave a deep  impression on the body. This psyche  spreads discord in the physical  level and upsets the balance and  functioning of the body. The  relationship between the emotions  and the digestion are established  in Psychology and psychosomatic  medicines. These harmful emotional  effects are detrimental and may lead  to psychosomatic diseases. English  Physician Dr, Edward Bach (1886- 1936) realized that for the formation  of chronic diseases, mind and  emotions are responsible factors.  He realized the different types of  mental and emotional states which  man experiences and tried to find the  remedies which could address these  emotions along with the imbalances.  There are 38 Bach remedies. These  remedies lift the emotions and thus  prevent the development of the  physical symptoms. If the physical  symptoms appear then physical  cure could be propelled. Bach  healers. The study of the people in  general, the clinical observation, the  bacteriological study and the power  stored in the plants together led to  the invention of Bach Remedies. The  lining and functioning of the bowel  are the seat of individual reaction of  the person along with the emotions.  For e.g. the abdomen typically  expresses grief by becoming numb  and dead. Anxiety and nervousness  are manifested by wrenching of the  bowels and elimination increase.
Keywords: psychosomatic medicines; man experiences; Bach Remedies; nervousness are manifested